Surface Roughness Evaluation of Resin Composites after Finishing and Polishing Using 3D-Profilometry - Alexandra Vinagre; Catarina Barros; Joana Gonçalves; Ana Messias; Filipe Oliveira; João Ramos (Hindawi Limited, 2023)
The purpose of this study was to evaluate the effect of two finishing and polishing methods on the surface roughness of different resin composites. Twenty-two disk-shaped specimens of five resin composites Zirconfill® (ZF), Filtek™ Supreme XTE (FS), Brilliant EverGlow™ (BG), Ceram.X® Duo (CD), and Harmonize™ (HA) were prepared for each one using a silicon mold. Both surfaces of each specimen were first grinded with 600-grit silicon carbide paper in a moistened environment. The polishing methods used included the two-step Enhance® and PoGo® polishing system (E/P) or the four-step SwissFlex® discs (SFD). Surface roughness was evaluated using a noncontact 3D-optical profilometer. Surface morphology was examined by scanning electron microscopy. Data were analyzed using two-way analysis of variance and pairwise comparisons with Tukey's test (α=0.050). Surface roughness was affected by both the type of resin composite (p<0.001) and the finishing and polishing system (p<0.001), with a significant interaction between these two factors (p=0.025). The E/P system produced smoother surfaces than the SFD system (p<0.001). For the E/P system, the highest mean roughness value was obtained with ZF and was statistically different from all other composites, whereas inhomogeneous results among resin composites could be found for the SFD system. Surface roughness was material-dependent, and the polishability of the resin composites was best accomplished using the E/P system. Within each F/P system studied, BG showed the lowest average surface roughness and ZF registered the highest.